2015
DOI: 10.1007/s00253-015-6795-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteome signatures—how are they obtained and what do they teach us?

Abstract: The dawn of a new Proteomics era, just over a decade ago, allowed for large-scale protein profiling studies that have been applied in the identification of distinctive molecular cell signatures. Proteomics provides a powerful approach for identifying and studying these multiple molecular markers in a vast array of biological systems, whether focusing on basic biological research, diagnosis, therapeutics, or systems biology. This is a continuously expanding field that relies on the combination of different meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 193 publications
0
11
0
Order By: Relevance
“…Second, an iTRAQbased proteomics method was employed to analyze the molecular targets of A549 cancer cells after TP treatment, and pathway and network analyses were performed. Proteomics analysis is a powerful tool for the identification of biological markers and estimation of biological networks [34]. A global view of the inter-connectivity of signaling proteins and their actions is critically important for successful lung cancer therapy [35] and should provide a comprehensive perspective for elucidating the roles of TP as a potential agent for treatment of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Second, an iTRAQbased proteomics method was employed to analyze the molecular targets of A549 cancer cells after TP treatment, and pathway and network analyses were performed. Proteomics analysis is a powerful tool for the identification of biological markers and estimation of biological networks [34]. A global view of the inter-connectivity of signaling proteins and their actions is critically important for successful lung cancer therapy [35] and should provide a comprehensive perspective for elucidating the roles of TP as a potential agent for treatment of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The Se20 strain contains a Ser83Tyr amino acid substitution in GyrA, which is the primary target in Gram‐negative bacteria. Target‐site gene mutations are the most common mechanism of high‐level fluoroquinolone resistance and although resistance is largely attributed to double mutations in the gyrA gene, high‐level resistance phenotypes have also been reported with single gyrA mutations . However, quinolone resistance is known to be multifactorial and other strategies such as reduced membrane permeability, increased production of multidrug‐resistance efflux pumps, modifying enzymes, and/or target‐protection proteins are of major importance for the overall resistance .…”
Section: Resultsmentioning
confidence: 99%
“…The acquisition of antibiotic resistance involves a complex interaction network that involves changes at the gene, transcript, protein, and metabolite level . Over the last years, proteomic tools have become established in the study of bacterial species providing quantitative and functional data to complement genomic and transcriptomic profiles . Numerous comparative proteomic studies, either of resistant bacteria or under antibiotic stress conditions, have shown the potential of these approaches not only in associating molecular changes to antibiotic resistance phenotypes but also in elucidating the mechanisms by which resistance arises .…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular binding was often transient and exhibited lower affinity than that of endogenous compounds (hormones) in a screening assay of protein array. 25,26 We could not find significant responses in the array when surface active reagent (Tween 20, 0.5%) was first used in the wash step; thus, we switched to milder phosphate buffer (20 mM) for washing. This modification enabled us to identify a total of 14 proteins as potential DOX-binding targets.…”
Section: Discussionmentioning
confidence: 99%